Unsuitability of indigenous South American Rutaceae as potential hosts of Diaphorina citri - de C Felisberto, Patrícia A [UNESP]; Girardi, Eduardo A; Peña, Leandro; Felisberto, Guilherme [UNESP]; Beattie, George AC; Lopes, Silvio A (Wiley, 2019)
BACKGROUND: ‘Candidatus Liberibacter asiaticus’ is transmitted by Diaphorina citri, an insect with a wide range of hosts in Rutaceae. Species related to Citrus occur in Brazilian forests where they may serve as hosts for psyllids and infested citrus orchards. RESULTS: The suitability of plants as hosts of D. citri was classified into four groups. Group I (high suitability): Citrus × aurantium ‘Valencia’, ‘Citrus limonia’, Murraya paniculata (syn. Murraya exotica L.) (Aurantioideae: Aurantieae) and Bergera koenigii (Aurantioideae: Clauseneae). Group II (intermediate to low suitability): Citrus (Poncirus) trifoliata ‘Pomeroy’, Citrus wintersii, Swinglea glutinosa (Aurantieae) and Clausena lansium (Clauseneae). Group III (not suitable): Aegle marmelos, Atalantia buxifolia, Citrus (‘Microcitrus’) sp. (Aurantieae) and Helietta apiculata (Amyridoideae). Group IV (non-hosts): Glycosmis pentaphylla (Clauseneae), Balfourodendron riedelianum, Casimiroa edulis, Esenbeckia febrifuga, Esenbeckia leiocarpa, Metrodorea stipularis, Zanthoxylum rhoifolium (Amyridoideae) and Dictyoloma vandellianum (Cneoroideae). Insects survived longer on newly differentiated leaves compared with fully expanded soft leaves. Psyllids either did not develop or did not survive for long on most Group IV species, all of which, with the exception of G. pentaphylla, occur naturally in Brazilian forests. CONCLUSION: Citrus relatives occurring in forests near citrus orchards are not suitable hosts of D. citri and, therefore, do not contribute to huanglongbing spread. © 2018 Society of Chemical Industry.
Keywords: Asian citrus psyllid; Aurantioideae; citrus greening; citrus relatives; host plants; huanglongbing